Strategi Dinas Pertanian Dan Kehutanan Kota Batu Dalam Meningkatkan Hasil Pertanian Tanaman Pangan - Teguh Junaedi (Jurnal Administrasi Publik, 2015)
Abstract: Strategy of Agriculture and Forestry Department Batu City in Improving Agriculture Produce of Food Crops. In fulfill people food needs, agriculture development should be conducted by Indonesian government. Agriculture development in Indonesia can’t be separated from many problems such as quality and quantity decrease of farming land resource and limited infrastructure availability aspect to support agriculture. The improvement of agriculture produce of food crops absolutely needed as food needs fulfillment. This condition leads the government of Batu City through Agriculture and Forestry Department to make strategy in improving agriculture produce of food crops. The strategy mentioned in strategic plan of Agriculture and Forestry Department Batu City in 2007-2012. With those strategies, it was proven that it could improve food crops production in Batu City in 2012 which reached up to 8.65% or for 7,404.8 tons compared in 2011 which only 6,815.50 tons. Keywords: agriculture development, improvement strategy of food crops produce Abstrak: Strategi Dinas Pertanian dan Kehutanan Kota Batu Dalam Meningkatkan Hasil Pertanian Tanaman Pangan. Dalam memenuhi kebutuhan akan pangan penduduk, Pembangunan pertanian harus dilakukan oleh pemerintah Indonesia. Pembangunan pertanian di Indonesia tidak terlepas dari berbagai macam masalah diantaranya penurunan kualitas dan kuantitas sumber daya lahan pertanian dan terbatasnya aspek ketersediaan infrastruktur penunjang pertanian. Peningkatan hasil pertanian tanaman pangan mutlak diperlukan sebagai pemenuhan kebutuhan akan pangan penduduk. Kondisi ini memicu pemerintah Kota Batu melalui Dinas Pertanian dan Kehutanan untuk membuat strategi-strategi peningkatan hasil pertanian tanaman pangan. Strategi tersebut tertuang dalam renstra Dinas pertanian dan kehutanan Kota Batu tahun 2007-2012. Dengan adanya strategi tersebut, terbukti bahwa dapat meningkatkan hasil produksi tanaman pangan padi di Kota batu pada tahun 2012 yang mencapai 8,65% atau sebesar 7.404,8 ton dibandingkan pada tahun 2011 yang hanya 6.815,50 ton. Kata kunci: pembangunan pertanian, strategi peningkatan hasil tanaman pangan